Challenges of Public Participation: A Qualitative Study - Suhaimi, Safiah (South Asian Journal of Social Sciences and Humanities, 2021)
The participation plays an important role among other people. When social participation is used today, a public participation will be rapid. The problem has happened when less participation of young people involved on youth associations. The youth has believed that they have still lacked the partcipation has needed for an effective participation and expressed little confidence in their involvement. This paper has analysed the challenges of public participation among youth associations. The methods that used a qualitative study by an interview for five youth associations in Kedah. Drawing on the final findings, two challenges which are: (i) financial and (ii) a less youth participation. Furthermore, the findings are expected to contribute to strengthening the youth associations to achieve good governance in the public participation.
Keywords: Challenges; Youth; Youth Participation; Public Participation; Governance.